2020
DOI: 10.29252/jha.23.3.11
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Job Satisfaction and Desire to Emigrate among the Nurses of Public Hospitals in Tehran

Abstract: The emigration process of nurses as the main human resources of the health system is worrying. The study aimed to determine the relationship between job satisfaction and the desire to emigrate among the nurses in Tehran. Methods: This correlational study was performed on the nurses of public hospitals in Tehran. We used random classified sampling to determine the hospitals. A research questionnaire was also used, including three sections: demographic information, job satisfaction, and desire to emigrate. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Furthermore, job satisfaction has been demonstrated to curtail turnover intentions within an organization and, likewise, diminish intentions to emigrate. The findings support the study conducted by Kamali et al. (2020), which suggested that when employees have a strong desire to emigrate, job satisfaction can act as a deterrent.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, job satisfaction has been demonstrated to curtail turnover intentions within an organization and, likewise, diminish intentions to emigrate. The findings support the study conducted by Kamali et al. (2020), which suggested that when employees have a strong desire to emigrate, job satisfaction can act as a deterrent.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, job satisfaction has been demonstrated to curtail turnover intentions within an organization and, likewise, diminish intentions to emigrate. The findings support the study conducted by Kamali et al (2020), which suggested that when employees have a strong desire to emigrate, job satisfaction can act as a deterrent. Furthermore, these results align with the research conducted by Ferreira et al (2020), which posited that job dissatisfaction can motivate physicians and nurses to seek emigration opportunities.…”
Section: Theoretical Contributionssupporting
confidence: 87%
See 1 more Smart Citation